Cross-sectional study of hepatitis B antibody status in health care workers immunized as children at an academic medical center in Wisconsin. Issue 7 (11th February 2020) - Ritscher, Alicia M.; LeClair-Netzel, Megan; Friedlander, Nicholas J.; Howard Stewart, Danielle N.; Wagner, Mallory; Kalscheur, Nicole; Caldera, Freddy; Hayney, Mary S.
Highlights: Sustained hepatitis B protection in 95% of healthcare workers immunized as infants. Males and infants younger than 7 months more likely to be vaccine non-responders. Consider a policy using hepatitis B vaccine series history as evidence of immunity. Abstract: Individuals who received the hepatitis B vaccine series as young children are entering the healthcare workforce. Our study measured the persistence of antibody to the hepatitis B surface antigen (anti-HBs) at time of employment. Among 986 individuals born in 1991 or more recently with documentation of completion of the hepatitis B vaccine series, 51% had anti-HBs < 10mIU/ml. Of these 507 healthcare workers, 446 (88%) received documented fourth dose of hepatitis B vaccine followed by another anti-HBs ≥ 28 days post vaccination; 11% (50/446 or 5% of the total population) did not mount an anamnestic response. The non-responders were more likely to be male or complete the vaccine series prior to age 7 months. Measuring anti-HBs at the time of hire in this population of healthcare workers who had documentation of hepatitis B series completion as young children may be unnecessary because of the high rate of hepatitis B vaccine protection.